2012
DOI: 10.1038/srep00512
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditioning in the control of macrophage thrombospondin-1 production

Abstract: Thrombospondin-1 (TSP-1) is a multifunctional protein which is secreted into the extracellular matrix during inflammation, where it modulates numerous components of the immune infiltrate. Macrophages are a source of TSP-1, which they produce in response to TLR4 mediated signals. Their production of TSP-1 is regulated by environmental signals that establish a threshold for the level of protein secretion that can be induced by LPS stimulation. Th1 and Th2 cytokines raise this threshold which leads to less TSP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
1
27
1
Order By: Relevance
“…Consistent with our earlier report, 16 these results further reinforce the assertion that M1 or M2 phenotype alone does not entirely determine functional outcome in promoting or regulating angiogenesis because macrophages integrate complex microenvironment and cytokine cues through time. 49 Although both Th2 cytokines drove sFlt-1 responses and induced macrophage-mediated inhibition on HUVEC proliferation, the effect of IL-4 was more pronounced. IL-4 and IL-13 trigger similar biological functions and signaling cascades, 50 and to demonstrate a requirement for signaling via the IL-4R we used BMDMs from IL-4 receptor-deficient mice and demonstrated that these cells failed to up-regulate sFlt-1 gene or protein expression when stimulated with recombinant IL-4 ( Figure 4).…”
Section: Il-4 Inhibition Of Angiogenesismentioning
confidence: 98%
“…Consistent with our earlier report, 16 these results further reinforce the assertion that M1 or M2 phenotype alone does not entirely determine functional outcome in promoting or regulating angiogenesis because macrophages integrate complex microenvironment and cytokine cues through time. 49 Although both Th2 cytokines drove sFlt-1 responses and induced macrophage-mediated inhibition on HUVEC proliferation, the effect of IL-4 was more pronounced. IL-4 and IL-13 trigger similar biological functions and signaling cascades, 50 and to demonstrate a requirement for signaling via the IL-4R we used BMDMs from IL-4 receptor-deficient mice and demonstrated that these cells failed to up-regulate sFlt-1 gene or protein expression when stimulated with recombinant IL-4 ( Figure 4).…”
Section: Il-4 Inhibition Of Angiogenesismentioning
confidence: 98%
“…Serine protease HTRA1/age related maculopathy susceptibility protein 2 genes are critical for the production of transforming growth factor, which plays an important role in the control of inflammation and interacts with matricellular proteins such as thrombospondin. 25 …”
Section: An Aging Retina Vs An Aging Immune Systemmentioning
confidence: 99%
“…TSP-1 is a major component of platelets alpha granules: pre-synthetised protein is released upon platelets activation (126, 127). Macrophages also regulate TSP-1 secretion: the secretion is induced by LPS, and the threshold for the level of secretion is regulated by the environmental signals, including the mediators of the adaptive immune system, Th1 and Th2 cytokines (128). TSP-1 secretion depends on cell density in culture: lower density results in higher secretion of TSP-1 by fibroblasts, endothelial and smooth muscle cells without change in protein synthesis (129).…”
Section: Introductionmentioning
confidence: 99%